When Austerity Didn't Work : A Case Study of Greece - Stamatiadis, Andreas (2016)
The aim of this thesis is to evaluate the austerity measures implemented by Greece during the Eurozone sovereign debt crisis. After providing information on the structural deficiencies of the Greek economy and how they created the crisis and affect economic growth, this thesis provides academic literature and empirical research on the austerity effects on the Greek economy and the Greek people. Furthermore, it criticizes austerity and the fallacies of the IMF, while also debating the Keynesian and supply-side approaches. The results show that albeit remarkable achievements in fiscal consolidation, austerity caused an ongoing recession, while failing to tackle existing structural problems of the Greek economy and increasing regional inequalities and deterioration of the Greek peoples physical and mental health.